Resisting state violence : radicalism, gender, and race in U.S. culture - James, Joy, 1958- (University of Minnesota Press, 1996)
African American scholar-activist Joy James offers a stimulating and iconoclastic account of a world in which the United States functions as the political-police center. Resisting State Violence is a clear-sighted and uncompromising guidebook for those who want to understand the forces that hinder social change, and to effectively move beyond them.